Novosecular Periphery of Nonspecific Art in the Artwork Ó by Nuno Ramos - Acevedo Rendón, Julián; Gil Blandón, Manuela (Disertaciones, 2020)
This article is originated in a project carried out in the research group “Literatura Marginales” (Marginalia) and its research line “Relecturas del canon literario”. The gaze is focused on the outlook of contemporary literature and its place within the postautonomy of contemporary art; in fact, the literary canon undergoes shocks and progressive modifications that lead to the loss of specificity in literary phenomena and to the dissolution of crystallized languages. The objective is to project an investigative stance on the problems that are part of the mode of organization of the sensible in contemporary literature (and that would allow us to speak of transformations and crises of notions that have been considered central to define art, namely belonging, specificity and autonomy). The conjecture converges with criticisms of a literary, philosophical, aesthetic, and sociological critical nature, such as: the literary work named Ó (2008) by the Brazilian artist Nuno Ramos; the literary critical dimension of the research text “Especie, especificidad y pertenencia” (2013a) of the Ph.D. Florencia Garramuño, and the philosophical considerations about the contemporaneity of Giorgio Agamben, Theodore Kaczynski’s sociological term "substitute activities", Mark Fisher’s position with his text Capitalist Realism (2016), are the corpus of antecedents that make up this critical postulate allowing to question the values and effects in narrative experimentation, and the periphery with which it must reconcile: industry, productivity and the literary canon.